2009
DOI: 10.1002/ibd.20907
|View full text |Cite
|
Sign up to set email alerts
|

Activation of NOD2-mediated intestinal pathway in a pediatric population with Crohnʼs disease

Abstract: In this study we provide for the first time ex vivo evidence of physiologically relevant protein interactions with NOD2, which are able to trigger the innate immune response in intestinal mucosal specimens of children with CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
33
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 40 publications
3
33
1
Order By: Relevance
“…For example, recent reports have demonstrated increased expression of both NOD2 and RIP2 and increased activation of RIP2 in the inflamed intestinal mucosa of a pediatric population with Crohn's disease (Stronati et al 2008;Negroni et al 2009). Likewise, the identified Blau Syndrome and Early Onset Sarcoidosis NOD2 polymorphisms have been described as gain-of-function mutations showing increased NF-kB activation basally and in response to NOD2 activation, presumably occurring through increased activation of RIP2 (Kanazawa et al 2005; for review, see Strober et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, recent reports have demonstrated increased expression of both NOD2 and RIP2 and increased activation of RIP2 in the inflamed intestinal mucosa of a pediatric population with Crohn's disease (Stronati et al 2008;Negroni et al 2009). Likewise, the identified Blau Syndrome and Early Onset Sarcoidosis NOD2 polymorphisms have been described as gain-of-function mutations showing increased NF-kB activation basally and in response to NOD2 activation, presumably occurring through increased activation of RIP2 (Kanazawa et al 2005; for review, see Strober et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, patients who harbor gain-of-function NOD2 alleles develop Blau Syndrome and sarcoidosis, two autoinflammatory granulomatous diseases (Miceli-Richard et al 2001;Chamaillard et al 2003;Schurmann et al 2003;Tanabe et al 2004;Kanazawa et al 2005). In addition to diseases of genetic NOD2 alteration, NOD2 has also been implicated in the pathogenesis of Crohn's disease in patients who do not harbor loss-of-function NOD2 alleles (Stronati et al 2008;Negroni et al 2009). In these patients, wild-type NOD2 expression and activity are increased, and it has been argued that this increase may help drive the inflammation present in pediatric Crohn's disease patients (Stronati et al 2008;Negroni et al 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, there are far greater numbers of CD patients who are WT for NOD2 than those who are polymorphic, and as NOD2 is regulated at the transcriptional level by NF-B (6), it has been suggested that increased expression of WT NOD2 may represent a feed-forward mechanism by which inflammation is exacerbated. Studies have demonstrated that CD patients with WT NOD2 demonstrate increased expression of both NOD2 and its associated kinase RIPK2 as well as increased RIPK2 kinase activity (7,8). In addition, compared with WT healthy controls, monocytes from CD patients WT for NOD2 show increased proinflammatory IL-8 secretion in response to MDP stimulation (9).…”
mentioning
confidence: 99%
“…15 For example, in pediatric CD, it has been shown that wild-type NOD2 and its obligate kinase RIP2 are overexpressed and hyperactive in ileitis. 46 Moreover, a recent study from Jamontt et al demonstrated that mice double deficient in IL-10 and NOD2 are protected from developing severe chronic colitis; they provide evidence that NOD2 contributes to enhanced proinflammatory activity of macrophages from IL-10 −/− mice and that the synergistic activity of MDP with TLR ligands in the absence of IL-10 renders macrophages intrinsically hyperresponsive to bacterial stimulus, thus contributing to the dysregulated immune environment that ultimately results in the development of colitis in IL-10 −/− mice. 47 In this context it has been postulated that inhibition of NOD2:RIP2 signaling in the presence of a wild-type NOD2 may be efficacious in CD.…”
mentioning
confidence: 99%